The taking of American Indian lands in the Southeast a history of territorial cessions and forced relocations, 1607-1840 - Miller, David W. (David Wesley), 1926- (McFarland & Co., Publishers, 2011)
"Between the time of the settling of Jamestown and the Trail of Tears in the 1830's, thousands of Native Americans were forced to cede land to European settlers and move westward. This book, with the aid of maps and pictures, relies primarily on the words of those involved to tell the tale of the transfer of land"--Provided by publisher.